2021
DOI: 10.1055/a-1362-9743
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the German Version of the Mind Excessively Wandering Scale (MEWS-G)

Abstract: Increasing evidence shows that unintentional mind wandering is linked to Attention Deficit Hyperactivity Disorder (ADHD) and that its frequency contributes to symptom severity and functional impairment in ADHD. However, empirical data on mind wandering in adult ADHD are still scarce, and a validated scale to assess mind wandering in German adult ADHD patients is lacking. The primary aim of this study is to assess the psychometric properties of the German version of the recently published Mind Excessively Wande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Unintentional mind wandering is common in ADHD and higher frequency of mind wandering is associated with increased functional impairment and related to lower EF ( 28 ). The Mind Excessively Wandering Scale (MEWS) consists of 15 items ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Unintentional mind wandering is common in ADHD and higher frequency of mind wandering is associated with increased functional impairment and related to lower EF ( 28 ). The Mind Excessively Wandering Scale (MEWS) consists of 15 items ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Confirmatory factor analysis (CFA) was subsequently conducted to compare the fit of factor structures derived from the hierarchical analysis, the 1-factor structure demonstrated in previous studies ( Mowlem et al, 2016 ; Nakovics et al, 2020 ) and other hierarchical solutions using the UK sample. CFA estimates were obtained using diagonally weighted least square algorithms due to the ordinal response scale of items and data distribution skewness ( DiStefano and Morgan, 2014 ; Li, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, the higher the RMSEA, the higher the probability of erroneously rejecting a more complex structure of covariances when explaining a construct. In this sense, Nakovics et al (2020) identified a 2-factorial scale structure solution when analyzing the psychometric properties of the German version of the MEWS. However, the authors argued that these two factors, namely “difficulties controlling own thoughts and focusing” (Factor 1) and “thought fluctuation” (Factor 2), were closely related and interdependent but not distinct facets of MW ( Nakovics et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations